2012
DOI: 10.1007/s10597-012-9506-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Weight Loss Program for Latino Outpatients with Severe Mental Illness

Abstract: To determine feasibility of implementation of a weight loss program for overweight Latinos with severe mental illness. In this quasi-experimental study, a 14-week behavioral weight loss course (extended) was implemented at one clinic. A one-time nutrition class (brief) was given at a sister clinic. Implementation feasibility was assessed by consent and participation rates. Weight was followed for 6 months. Consent rates were high [77 % (49/64) extended; 68 % (39/57) brief], and 88 % (43/49) of extended subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Only one study included non–English-speaking participants and culturally adapted the lifestyle intervention to fit the needs of a small group of Spanish-speaking Hispanic patients (26). Aside from Weber and colleagues' study (26), we know of one other quasi-experimental study that was recently completed that also adapted a lifestyle intervention for Hispanic outpatients with serious mental illness (48). More work in this area is clearly needed given the prevalence of racial and ethnic health disparities in the United States (49).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study included non–English-speaking participants and culturally adapted the lifestyle intervention to fit the needs of a small group of Spanish-speaking Hispanic patients (26). Aside from Weber and colleagues' study (26), we know of one other quasi-experimental study that was recently completed that also adapted a lifestyle intervention for Hispanic outpatients with serious mental illness (48). More work in this area is clearly needed given the prevalence of racial and ethnic health disparities in the United States (49).…”
Section: Discussionmentioning
confidence: 99%
“…67,68,70 A large VA study (N = 22,014) found that adherence to oral hypoglycemic medications was actually better among diabetes patients with schizophrenia than patients without schizophrenia (57 % vs. 48 %, p < 0.001). 71 Additionally, people with schizophrenia attend weight loss programs if these are provided, [72][73][74] although whether their attendance rates are comparable to those without SMI has not been studied.…”
Section: Management Of Type 2 Diabetes and Other Cardiovascular Diseamentioning
confidence: 99%
“…For interested participants, RAs will conduct a face-to-face screening interview to determine study eligibility, and for those eligible, obtain informed consent. Eligibility criteria (Table 1 ) are similar to the ones used in previous weight loss trials [ 27 , 28 ] and are broad in order to capture a sample that resembles racially/ethnically diverse people with SMI served by supportive housing agencies. RAs will then conduct baseline interviews face-to-face with eligible participants at their site within a week of recruitment.…”
Section: Methodsmentioning
confidence: 99%
“…More research has been done recently, but only in clinical settings. A study tested the acceptability and feasibility of a weight loss program among 43 Latino patients with SMI in an outpatient clinic [ 28 ], and the ACHIEVE trial sample was 38 % black. More work is needed given the growth of the national racial/ethnic minority population and the persistent health disparities they face.…”
Section: Introductionmentioning
confidence: 99%